2016
DOI: 10.1016/s2468-1253(16)30015-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 3-week response-guided triple direct-acting antiviral therapy for chronic hepatitis C infection: a phase 2, open-label, proof-of-concept study

Abstract: Summary Background To shorten the course of direct-acting antiviral agents for chronic hepatitis C virus (HCV) infection, we examined the antiviral efficacy and safety of 3 weeks of response-guided therapy with an NS3 protease inhibitor and dual NS5A inhibitor–NS5B nucleotide analogue. Methods In this open-label, phase 2a, single centre study, Chinese patients with chronic HCV genotype 1b infection without cirrhosis were randomly allocated by a computer program to one of three treatment groups (sofosbuvir, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 34 publications
(44 reference statements)
10
91
0
Order By: Relevance
“…A proof-of-concept clinical trial of triple-DAA treatment (10) also showed that SOF&DCV&SMV can achieve a high SVR rate, while reducing the treatment period from 12 wk to only 3 wk using a response-guided protocol. Our analysis clearly supports a clinical advantage for triple-DAA-based IFN-free treatments as discussed elsewhere (8,10,(20)(21)(22).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A proof-of-concept clinical trial of triple-DAA treatment (10) also showed that SOF&DCV&SMV can achieve a high SVR rate, while reducing the treatment period from 12 wk to only 3 wk using a response-guided protocol. Our analysis clearly supports a clinical advantage for triple-DAA-based IFN-free treatments as discussed elsewhere (8,10,(20)(21)(22).…”
Section: Resultssupporting
confidence: 83%
“…Additional drugs have just been approved, and others will eventually be approved for adding new combination choices (7). Anti-HCV treatment with triple-DAA regimens has also been in clinical trials (8)(9)(10).…”
mentioning
confidence: 99%
“…Whereas PR required 24–48 weeks of therapy and cured about 50% of chronic HCV patients treated, DAA combinations elicit nearly 100% cure with 12 weeks or less of therapy 2. Significant efforts are ongoing now to reduce the duration of treatment with DAAs without compromising treatment outcomes 3, 4. Indeed, treatments as short as 3 weeks have been shown to succeed in select populations 4.…”
Section: Introductionmentioning
confidence: 99%
“…It could also be used to explore age-based models that include further aspects of intracellular HCV life cycle such as translation positive-strand HCV RNA and the synthesis of positive and negative-strand HCV RNA [58]. Finally, since the current age-based HCV multiscale model is a successful milestone but still fails to predict cure in some DAA-treated patients [59][60][61], further model modification will be needed [38,39] and future developments would necessitate some updates in the numerical method. While such models become quickly overwhelming to solve analytically, an extension of the presented method is straightforward.…”
Section: Discussionmentioning
confidence: 99%